Driving indicators for implementation of sustainable procurement behavior and practices - Nadeem, Shahid; Mohamad, Mohamad Hanapi; Nik Abdullah, Nik Ab. Halim (www.euacademic.org, 2017)
Environmental issues have been universally accepted as the greatest threat to mankind and planet. States and organisations are implementing strategies and policies to address these issues. Sustainable public procurement (SPP) is considered as one of the strategy to mitigate the adverse environmental effects.Government of Pakistan has already taken few initiatives, and despite country leadership’s will, the pace of SPP implementation is low.In Pakistan there are regulations and legal frame work for procurement but there is lack of specific guide lines for procurement officers for implementations of SPP practices in Pakistan. There are numerous driving indicators but this study has shed light on effects of awareness, organizational commitment towards change and approach to green suppliers on sustainable procurement implementation.Finding from study on procurement managers working in government departments of Pakistan indicated that awareness and organizational commitment to change and approach to green supplier and products were positively related to sustainable public procurement implementation.These results implicate the need to create and enhance more awareness and organizational commitment more over availability of green supplier is needed to implement SPP successfully.The study may provide a useful insight for procurement managers and policy makers and can enable them to be successfully implemented the SPP practices in Pakistan.